PENANAMAN NILAI-NILAI KARAKTER PESERTA DIDIK DI SMA NEGERI 1 PADANG PANJANG - Zulhairi Zulhairi (IAIN Batusangkar, 2016)
This study was aimed at describing the strategy on building the students’ character values in high school 1 Padang Panjang. This study was qualitative by using interview, documentation and observation as instruments. The results revealed that the strategy on upgrading students’ character were applied in intracurricular and extracurricular. In intracurricular, there was morning mentoring program. In extracurricular, there were educational building through small group; night mentoring; Islamic orientation; memorizing quran; Friday praying; annual islamic day; Islamic hiking; Islamic Study Tour (IST); and Ramadhan School. To upgrade the students’ independent, the programs applied were 1) cleaning class; 2) cleaning room; 3) early wake up for praying tahajjud and subuh; 4) washing own clothes. Keywords: Strategy, Students’ Character Values, High School, Padang Panjang